Radial Distance Estimation with Tapered Whisker Sensors - Ahn, Sejoon (Sensors (Basel), 2017)
Rats use their whiskers as tactile sensors to sense their environment. Active whisking, moving whiskers back and forth continuously, is one of prominent features observed in rodents. They can discriminate different textures or extract features of a nearby object such as size, shape and distance through active whisking. There have been studies to localize objects with artificial whiskers inspired by rat whiskers. The linear whisker model based on beam theory has been used to estimate the radial distance, that is, the distance between the base of the whisker and a target object. In this paper, we investigate deflection angle measurements instead of forces or moments, based on a linear tapered whisker model to see the role of tapered whiskers found in real animals. We analyze how accurately this model estimates the radial distance, and quantify the estimation errors and noise sensitivity. We also compare the linear model simulation and nonlinear numerical solutions. It is shown that the radial distance can be estimated using deflection angles at two different positions on the tapered whisker. We argue that the tapered whisker has an advantage of estimating the radial distance better, as compared to an untapered whisker, and active sensing allows that estimation without the whisker’s material property and thickness or the moment at base. In addition, we investigate the potential of passive sensing for tactile localization.